Biological properties of influenza A virus mutants with amino acid substitutions in the HA2 glycoprotein of the HA1/HA2 interaction region. (22nd July 2019) - Jakubcová, L.; Vozárová, M.; Hollý, J.; Tomčíková, K.; Fogelová, M.; Polčicová, K.; Kostolanský, F.; Fodor, E.; Varečková, E.
Abstract : Influenza A viruses (IAVs) enter into cells by receptor-dependent endocytosis. Subsequently, conformational changes of haemagglutinin are triggered by low environmental pH and the N terminus of HA2 glycoprotein (gp) is inserted into the endosomal membrane, resulting in fusion pore formation and genomic vRNA release into the cytoplasm. However, the pH optimum of membrane fusion is host- and virus-specific and can have an impact on virus pathogenicity. We prepared mutants of neurotropic IAV A/WSN/33 (H1N1) with aa substitutions in HA2 gp at the site of HA1/HA2 interaction, namely T642 H (HA2 numbering position 64, H1 numbering position HA407; referred to as mutant '64'), V662 H ('66') (HA409); and a double mutant ('D') with two aa substitutions (T642 H, V662 H). These substitutions were hypothesized to influence the pH optimum of fusion. The pH optimum of fusion activity was measured by a luciferase assay and biological properties of viruses were monitored. The in vitro and in vivo replication ability and pathogenicity of mutants were comparable (64) or lower (66, D) than those of the wild-type virus. However, the HA2 mutation V662 H and double mutation T642 H, V662 H shifted the fusion pH maximum to lower values (ranging from 5.1 to 5.3) compared to pH from 5.4 to 5.6 for the wild-type and 64 mutant. The decreased replication ability and pathogenicity of 66 and D mutants was accompanied by higher titres in late intervals post-infection in lungs, and viral RNA in brains compared to wild-type virus-infected mice. These results have implications for understanding the pathogenicity of influenza viruses.